Faceless - Sheinmel, Alyssa B. (Scholastic Press, 2015)
Maisie is a normal sixteen-year-old, until an electrical fire caused by a lightning strike leaves her with severe burns, her face partially destroyed--she is lucky enough to get a full face transplant but she soon discovers how much her looks shaped her own identity and her relationship with those around her, including her boyfriend.